Six-Months Retention on Treatment and Attrition Risk Factors among People Living with HIV in Kibera Informal Settlement, Nairobi, Kenya - Samuel Opondo Muhula; John Gachohi; Yeri Kombe 3 (International Journal of Environmental Research and Public Health, 2022)
Early retention of patients on HIV treatment is vital in preventing new infections, reducing transmissions, preventing AIDS related deaths and achieving viral suppression. This study sought to determine the effectiveness of non-cash intervention (reminding HIV positive patients at every clinic visit that they stand to receive free T-shirts of their favorite football team or free Kiondos based on preference if they made it to the sixth month visit without missing a treatment appointment) and psychosocial support on retention during the first six months of HIV treatment. This unblinded randomized control trial was conducted at three health centers within the Kibera informal settlement in Nairobi, Kenya. Participants were randomly assigned to the intervention and control groups at a ratio of 1:1. Eligible participants were patients who newly tested HIV positive and enrolled for treatment at the study sites, were 18 years and older and were willing and able to provide informed consent to participate in the study. The primary outcome of interest was retention on treatment at six months. The overall retention on treatment at six months was 93%. Retention at six months among the intervention and control groups was 94% and 91%, respectively (aRR: 1.03; 95% CI: 0.98–1.09; p-value = 0.24). Attrition from treatment was significantly associated with being divorced, being single/never married, time to clinic, participant weight and being on other first line ART regimens other than TDF/3TC/DTG and TDF/3TC/EFV. Mortality and lost to follow-up rates were 1.6 and 13.5 per 100 person-years, respectively. The combination of non-cash incentives and psychosocial support did not improve retention during the first six months of HIV treatment. To reduce further attrition in the early stages of HIV treatment, innovative strategies are needed to reach divorced and not married/single patients earlier and support them to remain on treatment. Efforts should also be made to further decentralize ART treatment to reduce costs and time associated with travelling to and from hospitals
Keywords: HIV/AIDS; antiretroviral therapy; retention; attrition; Kenya